2017
DOI: 10.1038/s41598-017-17494-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ARNT-regulated BIRC3 as the target factor in cadmium renal toxicity

Abstract: Cadmium (Cd) is an environmental contaminant that exhibits renal toxicity. The target transcription factors involved in Cd renal toxicity are still unknown. In this study, we demonstrated that Cd decreased the activity of the ARNT transcription factor, and knockdown of ARNT significantly decreased the viability of human proximal tubular HK-2 cells. Microarray analysis in ARNT knockdown cells revealed a decrease in the expression of a number of genes, including a known apoptosis inhibitor, BIRC3, whose gene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 70 publications
0
48
0
Order By: Relevance
“…These results suggest that Cd may suppress BIRC3 gene expression specifical- ly in the kidney. Our previous research indicated that Cd-induced suppression of BIRC3 gene expression increased the level of the active form of caspase-3 (Lee et al, 2017). However, recent studies have shown that BIRC family members are functionally non-equivalent and regulate caspase activities via distinct mechanisms (Choi et al, 2009;Eckelman and Salvesen, 2006;Tenev et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that Cd may suppress BIRC3 gene expression specifical- ly in the kidney. Our previous research indicated that Cd-induced suppression of BIRC3 gene expression increased the level of the active form of caspase-3 (Lee et al, 2017). However, recent studies have shown that BIRC family members are functionally non-equivalent and regulate caspase activities via distinct mechanisms (Choi et al, 2009;Eckelman and Salvesen, 2006;Tenev et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research demonstrated that Cd inhibited ARNT transcription factor activity in human proximal tubular cells (HK-2 cells) (Lee et al, 2017). Furthermore, we showed that Cd decreased the gene expression of BIRC3, an apoptosis-inhibiting factor, through the suppression of ARNT activity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Protein/DNA arrays were used to identify transcription factors of which the activities are altered by nontoxic levels of Cd in NRK-52E and HK-2 cells. [27][28][29] Protein/DNA arrays screen a maximum of 345 transcription factors with activities that can be affected by a test substance. Cd downregulated the activity of a diverse set of transcription factors.…”
Section: Downregulates Ube2d Family Gene Expression Via Suppressiomentioning
confidence: 99%
“…[1][2][3][4] Our previous study demonstrated that cadmium, which causes chronic renal toxicity, induced apoptosis in human proximal tubular cells (HK-2 cells) and in the mouse kidney. 5,6) Strikingly, cadmium-induced apoptosis involves BIRC3 gene suppression. 5) BIRC3 is a member of the BIRC family of apoptosis inhibitors, which consists of eight family members in human and seven family members in mouse.…”
mentioning
confidence: 99%